Upaya Meningkatkan Hasil Belajar Mata Pelajaran PPKn Siswa Melalui Media Quizizz Kelas X di SMK N 1 Percut Sei Tuan - Cindy Nababan; Anjelina Pasaribu; Jamaludin Jamaludin; Sri Yunita (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research aims to improve learning outcomes in Civics subjects through the use of Quizizz media in class X at SMK N 1 Percut Sei Tuan. The research method used is classroom action research which is carried out in two cycles, each consisting of planning, implementation, observation and reflection. The subjects of this research were class X students of SMK N 1 Percut Sei Tuan. The data collection methods used were tests, observations and interviews. The research results show that the use of Quizizz media can significantly improve learning outcomes in Civics subjects. The results of this study show a significant increase in the learning outcomes of students who use Quizizz media compared to the control group. Apart from that, the use of Quizizz media also increases students' interest in learning and provides an interactive and fun learning experience. These findings indicate that the use of Quizizz media can be an effective alternative in improving learning outcomes in Civics subjects in vocational high schools.